Isolation, characterization and analysis of pro-inflammatory potential of Klebsiella pneumoniae outer membrane vesicles. (November 2019) - Martora, Francesca; Pinto, Federica; Folliero, Veronica; Cammarota, Marcella; Dell'Annunziata, Federica; Squillaci, Giuseppe; Galdiero, Massimiliano; Morana, Alessandra; Schiraldi, Chiara; Giovane, Alfonso; Galdiero, Marilena; Franci, Gianluigi
Abstract: Outer membrane vesicles (OMVs) are potent virulence factors, naturally secreted by gram-negative bacteria. Since Klebsiella pneumoniae has emerged as an important nosocomial pathogen, because of resistance to a wide spectrum of antibiotics, it is crucial to investigate its pathogenetic mechanism microorganism secretes outer membrane vesicles (OMVs), but the pathogenesis of Klebsiella pneumoniae as it relates to OMVs has not been well elucidated. In this study we focused on the isolation, characterization and evaluation of the virulence potential of OMVs obtained from Klebsiella pneumoniae . Our data demonstrate that Klebsiella pneumoniae OMVs are important secretory nanocomplexes that elicit a potent inflammatory response. Since OMVs are clearly involved in the pathogenesis of this bacterium during infection, further studies are required to determine whether they could be future targets for novel therapy and potential vaccine against Klebsiella pneumoniae. Highlights: Klebsiella pneumoniae is an important nosocomial pathogen. Klebsiella pneumoniae naturally secretes outer membrane vesicles (OMVs). Outer membrane vesicles are important secretory nanocomplexes. Klebsiella pneumoniae OMVs elicit a potent inflammatory response.